Jorge Mario Bergoglio and Abraham Skorka. On Heaven and Earth: Pope Francis on Faith, Family, and the Church in the Twenty-First Century - Ruiz, Jean-Pierre (Studies in Christian-Jewish Relations, 2014)
No abstract is available.